Editorial - Calizaya, Hugo Calizaya (2019)
Magazines continue to be the best means of dissemination of research work worldwide. They remain an essential means in a constantly evolving scientific structure. This edition enthusiastically covers the results of the research of the different master's and doctoral programs of the Graduate School of the Private University of Tacna, and this time with relevant social focus on problems of the regional environment. The magazine is designed for professionals interested in a wide range of topics of population and social interest, from engineering technologies to opinion in the development of socio-cultural characteristics. The edition includes the combination of skills that will always be in demand in the different aspects of scientific work, with a multidisciplinary integral vision approach. Already with his 3rd. Online edition, a much wider dissemination of the research carried out in our institution has been achieved.  We hope in future work to have the participation of inter-institutional networks, with the realization of joint efforts, common objectives and wider collaboration of professional peers. Dr. Hugo Calizaya Calizaya Director – Editor Veritas Et Scientia